Stochastic Simulations of Bed Topography Constrain Geothermal Heat Flow and Subglacial Drainage Near Dome Fuji, East Antarctica - Shackleton, Calvin; Matsuoka, Kenichi; Moholdt, Geir; Van Liefferinge, Brice; Paden, John (Journal of Geophysical Research: Earth Surface, 2023)
Abstract Topographic variability beneath ice sheets regulates ice flow, basal melting, refreezing processes, and meltwater drainage. The preservation of old ice layers and basal ice stratigraphy is sensitive to these subglacial processes, and Dome Fuji, inland East Antarctica, is one of the few regions where 1.5-Ma old ice can be preserved for investigating a major climatic change that occurred in the mid-Pleistocene. We used stochastic simulation methods and radar data to generate an ensemble of simulated bed topography with the continuous and realistic roughness necessary to assess basal conditions. Ensemble analysis reveals the magnitude and spatial distribution of topographic uncertainty, facilitating uncertainty-constrained assessments of subglacial drainage and topographic adjustments to geothermal heat flow (GHF). We find that topographic variability can lead to widespread local GHF variations of ±20% of the background value, which aggregate to raise the regional value and suggest previously underestimated distributions and rates of basal melting. We also find that survey profile spacing has an increasing influence on topographic uncertainty for rougher bed, deriving an empirical relationship that could guide future survey planning based on uncertainty tolerance.
_eprint: https://agupubs.onlinelibrary.wiley.com/doi/pdf/10.1029/2023JF007269
Keywords: Dronning Maud Land; glasiologi; hydrologi

A Mobile, Multichannel, UWB Radar for Potential Ice Core Drill Site Identification in East Antarctica: Development and First Results - Rodriguez-Morales, Fernando; Braaten, David; Trong Mai, Hoang; Paden, John; Gogineni, Prasad; Yan, Jie-Bang; Abe-Ouchi, Ayako; Fujita, Shuji; Kawamura, Kenji; Tsutaki, Shun; Liefferinge, Brice Van; Matsuoka, Kenichi; et al. (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing, 2020)
We developed a high-performance, multichannel, ultra-wideband radar system for measurements of the base and interior of the East Antarctic Ice Sheet. We designed the radar to be of high power (4000-W peak) yet portable and to be able to operate with 60-MHz bandwidth at a center frequency of 200 MHz, providing high sensitivity and fine vertical resolution relative to current technology. We used the radar to perform extensive measurements as a part of a multinational collaboration. We collected data onboard a tracked vehicle outfitted with an array of high-gain antennas. We sounded 2- to 3-km thick ice near Dome Fuji. Preliminary ice thickness data match those obtained via semicoincident measurements performed with a different surface-based pulse modulated radar system operated during the same field campaign, as well as previous airborne measurements. In addition, we mapped internal reflection horizons with fine vertical resolution from 300 m below the ice surface to ∼100 m above the bed. In this article, we provide a detailed overview of the radar instrument design, implementation, and field measurement setup. We present sample data to illustrate its capabilities and discuss how the data collected with it will be valuable for the assessment of promising drilling sites to recover ice cores that are 0.9–1.5 million years old.
Keywords: Antarktis; glasiologi; innlandsis; iskjerner

Deep glacial troughs and stabilizing ridges unveiled beneath the margins of the Antarctic ice sheet - Morlighem, Mathieu; Rignot, Eric; Binder, Tobias; Blankenship, Donald; Drews, Reinhard; Eagles, Graeme; Eisen, Olaf; Ferraccioli, Fausto; Forsberg, René; Fretwell, Peter; Goel, Vikram; Greenbaum, Jamin S; et al. (Nature Geoscience, 2020)
The Antarctic ice sheet has been losing mass over past decades through the accelerated flow of its glaciers, conditioned by ocean temperature and bed topography. Glaciers retreating along retrograde slopes (that is, the bed elevation drops in the inland direction) are potentially unstable, while subglacial ridges slow down the glacial retreat. Despite major advances in the mapping of subglacial bed topography, significant sectors of Antarctica remain poorly resolved and critical spatial details are missing. Here we present a novel, high-resolution and physically based description of Antarctic bed topography using mass conservation. Our results reveal previously unknown basal features with major implications for glacier response to climate change. For example, glaciers flowing across the Transantarctic Mountains are protected by broad, stabilizing ridges. Conversely, in the marine basin of Wilkes Land, East Antarctica, we find retrograde slopes along Ninnis and Denman glaciers, with stabilizing slopes beneath Moscow University, Totten and Lambert glacier system, despite corrections in bed elevation of up to 1 km for the latter. This transformative description of bed topography redefines the high- and lower-risk sectors for rapid sea level rise from Antarctica; it will also significantly impact model projections of sea level rise from Antarctica in the coming centuries.
Keywords: Antarktis; glasiologi; innlandsis; klimaendringer

Bedmap3 updated ice bed, surface and thickness gridded datasets for Antarctica - Pritchard, Hamish D.; Fretwell, Peter T.; Fremand, Alice C.; Bodart, Julien A.; Kirkham, James D.; Aitken, Alan; Bamber, Jonathan; Bell, Robin; Bianchi, Cesidio; Bingham, Robert G.; Blankenship, Donald D.; Casassa, Gino; et al. (Scientific Data, 2025)
We present Bedmap3, the latest suite of gridded products describing surface elevation, ice-thickness and the seafloor and subglacial bed elevation of the Antarctic south of 60 °S. Bedmap3 incorporates and adds to all post-1950s datasets previously used for Bedmap2, including 84 new aero-geophysical surveys by 15 data providers, an additional 52 million data points and 1.9 million line-kilometres of measurement. These efforts have filled notable gaps including in major mountain ranges and the deep interior of East Antarctica, along West Antarctic coastlines and on the Antarctic Peninsula. Our new Bedmap3/RINGS grounding line similarly consolidates multiple recent mappings into a single, spatially coherent feature. Combined with updated maps of surface topography, ice shelf thickness, rock outcrops and bathymetry, Bedmap3 reveals in much greater detail the subglacial landscape and distribution of Antarctica’s ice, providing new opportunities to interpret continental-scale landscape evolution and to model the past and future evolution of the Antarctic ice sheets.
Article Number: 414
Keywords: Antarktis; geofysikk; geomorfologi; glasiologi; hydrologi; oseanografi